2002
DOI: 10.1074/jbc.m205289200
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Changes in the Aged Brain Are Triggered by Interleukin-1β-induced Activation of p38 and Reversed by Treatment with Eicosapentaenoic Acid

Abstract: Among the several changes that occur in the aged brain is an increase in the concentration of the proinflammatory cytokine interleukin-1␤ that is coupled with a deterioration in cell function. This study investigated the possibility that treatment with the polyunsaturated fatty acid eicosapentaenoic acid might prevent interleukin-1␤-induced deterioration in neuronal function. Assessment of four markers of apoptotic cell death, cytochrome c translocation, caspase-3 activation, poly-(ADP-ribose) polymerase cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
98
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 53 publications
13
98
0
1
Order By: Relevance
“…Cell biological and molecular studies suggest that omega-3 fatty acids modulate membrane fluidity (Hashimoto et al, 1999), dopaminergic (Piomelli, 1994) and serotonergic (Yao et al, 2004) neurotransmission, and differentially alter gene expression (Kitajka et al, 2002;Salvati et al, 2004). Furthermore, preclinical studies suggest that omega-3 fatty acids have neuroprotective properties Lynch et al, 2007;Martin et al, 2002). Animal and human studies provide ample evidence that essential fatty acid deprivation during pregnancy is associated with developmental and behavioral abnormalities (Innis et al, 1999;Wainwright et al, 1994a, b) that are ameliorated by essential fatty acid supplementation (Helland et al, 2003;Wainwright et al, 1994a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Cell biological and molecular studies suggest that omega-3 fatty acids modulate membrane fluidity (Hashimoto et al, 1999), dopaminergic (Piomelli, 1994) and serotonergic (Yao et al, 2004) neurotransmission, and differentially alter gene expression (Kitajka et al, 2002;Salvati et al, 2004). Furthermore, preclinical studies suggest that omega-3 fatty acids have neuroprotective properties Lynch et al, 2007;Martin et al, 2002). Animal and human studies provide ample evidence that essential fatty acid deprivation during pregnancy is associated with developmental and behavioral abnormalities (Innis et al, 1999;Wainwright et al, 1994a, b) that are ameliorated by essential fatty acid supplementation (Helland et al, 2003;Wainwright et al, 1994a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Following a period of stabilisation, test shocks were delivered at 30 second intervals and stable baseline responses were recorded for 10 minutes prior to tetanic stimulation which was delivered 1 hour after intrahippocampal injection. The tetanus consisted of 3 trains of highfrequency stimuli (250 Hz for 200 ms; 30 second inter-train interval) delivered to the perforant path and following this stimulation, recording at test shock frequency resumed for the remainder of the experiment (Martin et al, 2002). Animals were killed by cervical dislocation and this was 2 hours after intrahippocampal injection.…”
Section: Analysis Of Ltp In Vivomentioning
confidence: 99%
“…An inhibitory effect of TNF-␣ on LTP has also been reported (Butler et al, 2004;Cumiskey et al, 2007;Tancredi et al, 1992) and it has been identified as a key mediator in the inhibitory effect of A␤ on LTP (Rowan et al, 2007). Recent evidence has indicated that when inflammatory and oxidative stress are inhibited by overexpression of mitochondrial transcription factor A (TFAM), the age-related decrease in LTP in CA1 is ameliorated (Hayashi et al, 2008), while eicosapentaenoic acid, which exerts anti-inflammatory and antioxidative effects similarly restores LTP in aged rats Martin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%